ITV services for socializing in public places - Almeida, Pedro (2011)
Watching TV in public locations is very different from watching at Home, but it can also be a worthy experience, especially in the context of certain collective events, such as live football. The increasingly rich features of iTV services may even provide the ground for making the Television infrastructure an alternative framework for the deployment of public display services. In this paper, we present and discuss integration scenarios in which the iTV infrastructure and public display services conceived for multi-user interaction in public spaces are combined to generate new types of services offer. It reveals a considerable potential on the idea of leveraging iTV infrastructures for supporting new types of public display services benefiting from content generated and social interactions of the co-located audience. The successful use of these approaches will require a clear understanding of the properties of the iTV infrastructure and a focus on the type of applications in which those properties may provide more added-value than limitations.